Workshop Penulisan Artikel Penelitian Tindakan Kelas Bagi Guru - Putri Panjaitan, Ruqiah Ganda; Indrayani, Yuliati; Utomo, Kiki Prio; Hiendro, Ayong; Hendri, M. Irfani; Setyawati, Dina (Universitas Pahlawan Tuanku Tambusai, 2025)
The success of education is greatly influenced by the role of teachers, not only as educators but also as professionals who continuously improve their competencies through reflection and research, one of which is through Classroom Action Research (CAR). This CAR is conducted by teachers to improve the quality of learning and solve problems in the classroom. Despite its importance, many teachers still experience difficulties in writing CAR articles, mainly due to a lack of training in scientific writing. Therefore, this workshop was held to improve academic skills and encourage active participation in scientific writing. This workshop was held offline with 10 teachers. The activity included four main stages: initial planning, socialization, presentation of material by resource persons, discussion and question and answer sessions, and evaluation through post-tests and participant testimonials. The results showed that this workshop was effective in improving teachers' understanding and skills in writing CAR articles.